Food Sustainability, Environmental Awareness, and Adaptation and Mitigation Strategies for Developing Countries - Al-Baarri, Ahmad Nimatullah (Advances in Environmental Engineering and Green Technologies, 2023)
LCSH: Sustainability--Developing countries. | Food